Human pegivirus (HPgV) infection in Ghanaians co-infected with human immunodeficiency virus (HIV) and hepatitis B virus (HBV) - N’Guessan, K.F.; Boyce, C.; Kwara, A.; Archampong, T.N.A.; Lartey, M.; Sagoe, K.W.; Kenu, E.; Obo-Akwa, A.; Blackard, J.T. (Springer New York LLC, 2018)
Human pegivirus (HPgV) is a positive single-stranded RNA virus in the Flaviviridae family. Phylogenetic analysis reveals the presence of multiple HPgV genotypes with distinct geographic locations. HPgV is of interest because of its potential beneficial impact on HIV disease progression. Despite this, the effects of HPgV in the context of other viral infections, such as hepatitis B virus (HBV), are poorly understood, and data from resource-limited settings are scarce. Therefore, we conducted a cross-sectional analysis of HPgV in HIV/HBV co-infected patients in Ghana. Sera from 100 HIV/HBV co-infected individuals were evaluated for HPgV RNA, and the genotype determined by sequencing the 5′ untranslated region. HPgV RNA was detected in 27 samples (27%). Of these, 26 were genotyped successfully with 23 belonging to HPgV genotype 1 and 3 belonging to HPgV genotype 2. The presence of HPgV RNA had no statistically significant impact on CD4 cell count or HBV DNA titers in the HIV/HBV co-infected patients. However, there was a trend towards decreased HBV DNA levels in HPgV RNA-positive patients with CD4 cell count < 200 (p = 0.0626). HPgV co-infection is common in Ghana. The effect of HPgV on HIV or HBV disease among HIV/HBV co-infected patients was minimal. However, decreased HBV DNA levels in HPgV RNA-positive patients with low CD4 cell counts highlight the need for prospective studies of HPgV in HIV and hepatitis co-infected patients, especially in those with advanced HIV disease, to study further the effects of HPgV on liver disease. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Africa; GB virus C (GBV-C); Ghana; Hepatitis B virus (HBV); Pegivirus (HPgV)